2014
DOI: 10.7205/milmed-d-13-00317
|View full text |Cite
|
Sign up to set email alerts
|

Deployment-Related Risk Factors of Low Back Pain: A Study Among Danish Soldiers Deployed to Iraq

Abstract: Where much is known about the consequences of spinal and low back pain (LBP) during military deployments, there is lesser knowledge of risk factors for LBP among the deployed forces. The objective of this study was to identify deployment-related exposures associated with LBP. The study was a questionnaire-based cohort study among 1,931 Danish soldiers deployed to Iraq. Of the 680 respondents, 175 (26%) reported LBP. The population of respondents was adjusted for potential nonresponse bias. The associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
3
7
0
1
Order By: Relevance
“…They reported individuals who perceived the work situation as stressful (OR = 3.47, CI = 1.24 -9.74, p<0.05) has the strongest psychosocial association to LBP. This finding was supported by Nissen et al [7] in which they discovered that there is moderate association between psychological stress and LBP (OR = 1.71, p = 0.009). According to Nissen et al [7], studies in civilian cohorts, also shows similar findings in which there is strong relationship between self-reported stress and LBP.…”
Section: Psychosocial Risk Factors Of Lbp In the Militarysupporting
confidence: 61%
See 4 more Smart Citations
“…They reported individuals who perceived the work situation as stressful (OR = 3.47, CI = 1.24 -9.74, p<0.05) has the strongest psychosocial association to LBP. This finding was supported by Nissen et al [7] in which they discovered that there is moderate association between psychological stress and LBP (OR = 1.71, p = 0.009). According to Nissen et al [7], studies in civilian cohorts, also shows similar findings in which there is strong relationship between self-reported stress and LBP.…”
Section: Psychosocial Risk Factors Of Lbp In the Militarysupporting
confidence: 61%
“…This finding was supported by Nissen et al [7] in which they discovered that there is moderate association between psychological stress and LBP (OR = 1.71, p = 0.009). According to Nissen et al [7], studies in civilian cohorts, also shows similar findings in which there is strong relationship between self-reported stress and LBP. Feuerstein et al [17] developed a model which suggested ergonomic exposure (heavy lifting & carrying, prolonged sitting & standing, repetitive bending, pushing & pulling) does not directly influence LBP clinic visits but affects the military personnel work environment perception which are related to LBP clinic visits.…”
Section: Psychosocial Risk Factors Of Lbp In the Militarysupporting
confidence: 61%
See 3 more Smart Citations